Deep low-salinity groundwater in sedimentary basins: petrophysical methods from a case study in Somalia - Quiroga, E; Bertoni, C; Ruden, F (Springer Nature, 2023)
Oil and gas exploration data for the Northern Somalia and Horn of Africa region have been utilised for deep freshwater resources exploration. This unique geophysical and petrophysical dataset is integrated into a regional hydrogeological study and it allows for targeting of unmapped and unknown deep aquifers that would otherwise be beyond the conventional reach of the groundwater sector. The database includes open-hole well logging surveys (resistivity, gamma ray, and spontaneous potential), mud logging and drill stem test (DST) data. The results from the data analysis are combined with the geological interpretation to assess the freshwater potential of each mapped hydrostratigraphic unit in the region. The results highlight the presence of several previously unknown deep low-to-medium salinity (<9 g/L total dissolved solids (TDS)) aquifers within the Jurassic to Eocene units, including the Adigrat, Hamanlei, Gabredarre, Gumburo, Jessoma, and Auradu formations. With tested intervals of water containing less than 3.8 g/L total dissolved solids, the Auradu, Jessoma, and Gumburo formations are the most promising deep freshwater aquifers. Additional results on the analysis of groundwater parameters, such as hydraulic head, provide the basis for further groundwater modelling. The results show that the method has good potential, in particular for use in drought-stricken areas of arid regions. Ultimately, the results from this region have global significance, as the method can provide a new means of boosting fresh groundwater resources in water-poor regions, and supporting sustainable development and utilization of the resources in the medium and long term.